Practical cooling strategies during continuous exercise in hot environments: A systematic review and meta-analysis - Ruddock, A.; Robbins, B.; Tew, G.; Bourke, L.; Purvis, A. (Sports Medicine, 2017)
Performing exercise in thermally stressful environments impairs exercise capacity and performance. Cooling during exercise has the potential to attenuate detrimental increases in body temperature and improve exercise capacity and performance. Objective: The objective of this review was to assess the effectiveness of practical cooling strategies applied during continuous exercise in hot environments on body temperature, heart rate, whole body sweat production, rating of perceived exertion (RPE), thermal perception and exercise performance. Methods: Electronic database searches of MEDLINE, SPORTDiscus, Scopus and Physiotherapy Evidence Database (PEDro) were conducted using medical subject headings, indexing terms and keywords. Studies were eligible if participants were defined as `healthy`, the exercise task was conducted in an environment =25 °C, it used a cooling strategy that would be practical for athletes to use during competition, cooling was applied during a self-paced or fixed-intensity trial, participants exercised continuously, and the study was a randomised controlled trial with the comparator either a thermoneutral equivalent or no cooling. Data for experimental and comparator groups were meta-analysed and expressed as a standardised mean difference and 95 % confidence interval. Results: Fourteen studies including 135 participants met the eligibility criteria. Confidence intervals for meta-analysed data included beneficial and detrimental effects for cooling during exercise on core temperature, mean skin temperature, heart rate and sweat production during fixed-intensity exercise. Cooling benefited RPE and thermal perception during fixed-intensity exercise and improved self-paced exercise performance. Conclusion: Cooling during fixed-intensity exercise, particularly before a self-paced exercise trial, improves endurance performance in hot environments by benefiting RPE and thermal perception, but does not appear to attenuate increases in body temperature.